Fleet Carrier in Name or Fact?: The Post-War Misinterpretation of USS Ranger as Unsuitable for Combat in the Pacific - Alvey, James (The Northern Mariner / Le marin du nord, 2024)
Since World War Two, the USS Ranger (CV-4) has become perceived as incapable of combat in the Pacific Theater. Digitization has provided a new opportunity to examine its perception by commanders responsible for the carrier’s employment. These records reveal that the common perception of the carrier stemmed from diplomatic necessity, from an overworked bureau uneager for additional projects, and from commands eager to acquire Ranger for non-combat duty. Ranger was considered by the US Navy as fit for combat in the Pacific Theater during WWII, but other requirements overrode the need for one additional combatant carrier in the Pacific. À la suite de la Seconde Guerre mondiale, l’USS Ranger(CV-4) était considéré comme un porte-avions incapable de combattre dans le théâtre du Pacifique. La numérisation a permis aux commandants responsables de l’emploi du porte-avions d’examiner cette perception sous un nouvel angle. Ces documents révèlent que la perception commune du porte-avions provenait de la nécessité diplomatique, d’un bureau surchargé de travail qui voulait éviter des projets supplémentaires et de commandements désireux d’acquérir le Ranger pour des tâches non combattantes. La marine américaine considérait le Ranger comme étant apte au combat dans le théâtre du Pacifique pendant la Seconde Guerre mondiale, mais d’autres exigences l’ont emporté sur la nécessité d’avoir un porte-avions de combat supplémentaire dans le Pacifique.